Molecular dynamics simulation of proteins under high pressure: Structure, function and thermodynamics - Hata, Hiroaki; Nishiyama, Masayoshi; Kitao, Akio (Biochimica et biophysica acta. General subjects, 2020)
Molecular dynamics (MD) simulation is well-recognized as a powerful tool to investigate protein structure, function, and thermodynamics. MD simulation is also used to investigate high pressure effects on proteins. For conducting better MD simulation under high pressure, the main issues to be addressed are: (i) protein force fields and water models were originally developed to reproduce experimental properties obtained at ambient pressure; and (ii) the timescale to observe the pressure effect is often much longer than that of conventional MD simulations. First, we describe recent developments in MD simulation methodologies for studying the high-pressure structure and dynamics of protein molecules. These developments include force fields for proteins and water molecules, and enhanced simulation techniques. Then, we summarize recent studies of MD simulations of proteins in water under high pressure. Recent MD simulations of proteins in solution under pressure have reproduced various phenomena identified by experiments using high pressure, such as hydration, water penetration, conformational change, helix stabilization, and molecular stiffening. MD simulations demonstrate differences in the properties of proteins and water molecules between ambient and high-pressure conditions. Comparing the results obtained by MD calculations with those obtained experimentally could reveal the mechanism by which biological molecular machines work well in collaboration with water molecules. [Display omitted] •MD simulations demonstrate property differences of proteins and water between ambient and high-pressure conditions.•The TIP4P/2005 water model better reproduces pressure- dependent quantities of protein in solution.•Microsecond-long MD observes conformational transitions of proteins by pressure.•Enhanced samplings simulate large pressure-induced changes of protein conformation.•MD reveals that two amino acid differences allows pressure adaptation of deep-sea fish actins.